Sleep architecture in response to a late evening competition in team-sport athletes - Vitale, J. A.; Galbiati, A.; De Giacomi, G.; Tornese, D.; Levendowski, D.; Ferini-Strambi, L.; Banfi, G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The aim of this study was to assess the effect of a late evening competition on sleep characteristics and perceived recovery in team-sport players using a validated self-applicable and portable polysomnographic device. Methods: Sixteen team-sport players (age: 25.4 [1.4] y; body mass index: 23.6 [0.5] kg/m2) completed the study. Objective and subjective sleep data were collected for 4 consecutive nights: 2 nights before (PRE2 and PRE1) and the 2 nights after an evening match (POST1), performed between 6:00 PM and 9:00 PM. Total quality of recovery values were also collected in the morning.